2012
DOI: 10.1038/mp.2012.164
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association study identifies a potent locus associated with human opioid sensitivity

Abstract: Opioids, such as morphine and fentanyl, are widely used as effective analgesics for the treatment of acute and chronic pain. In addition, the opioid system has a key role in the rewarding effects of morphine, ethanol, cocaine and various other drugs. Although opioid sensitivity is well known to vary widely among individual subjects, several candidate genetic polymorphisms reported so far are not sufficient for fully understanding the wide range of interindividual differences in human opioid sensitivity. By con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
73
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 97 publications
(75 citation statements)
references
References 44 publications
1
73
1
Order By: Relevance
“…Another GWAS study reported that the C allele of rs2952768 in the Chr2q33.3 was associated with more analgesic requirements in human (Nishizawa et al., 2014). Multiple GWAS studies have proposed genes ( PRDM16 , TRPM8 or LRP1 ) and locus (Chr8q22.1) to be involved in the migraine (Anttila et al, 2010; Chasman et al., 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Another GWAS study reported that the C allele of rs2952768 in the Chr2q33.3 was associated with more analgesic requirements in human (Nishizawa et al., 2014). Multiple GWAS studies have proposed genes ( PRDM16 , TRPM8 or LRP1 ) and locus (Chr8q22.1) to be involved in the migraine (Anttila et al, 2010; Chasman et al., 2011).…”
Section: Discussionmentioning
confidence: 99%
“…For the analysis of personality profile data from healthy volunteer subjects, raw TCI scores were processed according to a previous report (33). The score on each subscale in each dimension was averaged, in which the total score was divided by the number of items in each subscale.…”
Section: Resultsmentioning
confidence: 99%
“…The TCI used in the present study was based on the shortened 125-item questionnaire of the longer 240-item Japanese version of the TCI. The usage of the TCI for the analysis in the present study is detailed in the Supplementary Materials and Methods and a previous report (33).…”
Section: Data Collectionmentioning
confidence: 99%
See 2 more Smart Citations